Development of 99Mo/99mTc Generator System for Production of Medical Radionuclide 99mTc using a Neutron-activated 99Mo and Zirconium Based Material (ZBM) as its Adsorbent - I. Saptiama; E. Lestari; E. Sarmini; H. Lubis; M Marlina; A. Mutalib (Atom Indonesia, 2016)
Molybdenum produced from fission of U-235 is the most desirable precursor for 99Mo/99mTc generator system as it is non-carrier added and has high specific activity. However, in the last decade there has been short supply of 99Mo due to several constrains. Therefore, there have been many works performed for development of 99Mo/99mTc generator system using 99Mo which is not produced from either LEU or HEU. This report deals with development of 99Mo/99mTc generator system where zirconium-based material (ZBM) is used as adsorbent of neutron-activated 99Mo. The system was prepared by firstly irradiating natural Mo in the G. A. Siwabessy reactor to produce neutron-activated 99Mo. The target was dissolved in NaOH 4N and then neutralized with 12 M HCl. The 99Mo solution was then mixed with a certain amount of ZBM followed by heating at 90°C for three hours to allow the 99Mo adsorbed on ZBM. The 99Mo-ZBM (9.36 GBq of 99Mo was Mo/ 4.2 g ZBM) was packed on a fritz-glass column. This column was then fitted serially with an alumina column for trapping 99Mo breakthrough. The columns were then eluted daily with saline solution for up to one week. The yield of 99mTc was found to be between 53.7 – 74% (n= 5). All 99mTc eluates were clear solutions with pH of 5. Breakthrough of 99Mo in 99mTc eluates was found to be 0.031 ± 0.019 μCi 99Mo/ mCi 99mTc (n= 5) which was less than the maximum activity of 99Mo allowed in 99mTc solution (< 1 µCi 99Mo/mCi 99mTc). Aluminum breakthrough in 99mTc eluates was found to be less than 10 ppm. The radiochemical purity of 99mTc in form of Na99mTcO4 was > 99%. Radiolabeling of this 99mTc towards methylene diphosphonate (MDP) kit gave a radiolabelling efficiency of 99%. In summary, a new 99Mo/99mTc generator system that used neutron-activated 99Mo and ZBM as its adsorbent has been successfully prepared. The 99mTc produced from this new 99Mo/99mTc generator system attained the quality of 99mTc required for medical purposes.Received: 23 Februari 2016; Revised: 13 July 2016; Accepted: 17 July 2016